2016
DOI: 10.1155/2016/5368793
|View full text |Cite
|
Sign up to set email alerts
|

Relative Susceptibilities of ABO Blood Groups toPlasmodium falciparumMalaria in Ghana

Abstract: The clinical outcome of falciparum malaria in endemic areas is influenced by erythrocyte polymorphisms including the ABO blood groups. Studies have reported association of ABO blood group to resistance, susceptibility, and severity of P. falciparum malaria infection. Individuals with blood group “A” have been found to be highly susceptible to falciparum malaria whereas blood group “O” is said to confer protection against complicated cases. We analyzed samples from 293 young children less than six years old wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
3
13
0
2
Order By: Relevance
“…Notwithstanding the foregoing, the mean parasitemia in blood recipients of blood group O was less than that in recipients of group A (2068 vs. 3859 parasites/µL of blood). This confirms that blood group A is very susceptible to P. falciparum infection than blood group O (Panda et al 2011 ; Afoakwah et al 2016 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Notwithstanding the foregoing, the mean parasitemia in blood recipients of blood group O was less than that in recipients of group A (2068 vs. 3859 parasites/µL of blood). This confirms that blood group A is very susceptible to P. falciparum infection than blood group O (Panda et al 2011 ; Afoakwah et al 2016 ).…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, it has also been established that anemia, especially iron deficiency anemia, increases susceptibility to infectious diseases (Beard 2001 ). Individuals with blood groups A and B were found to be highly susceptible to P. falciparum infection in several studies (Panda et al 2011 ; Afoakwah et al 2016 ). However, in this study, the frequency of incidence of P. falciparum infection was found to be high in blood group O.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the incidence of this blood group is very high in tropical regions of the world where infectious diseases are common [ 55 ]. The clinical importance of this distribution is illuminated by the low malaria parasitemia seen in individuals with the blood group O who live in West Africa [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it has yet to be fully established the validity or otherwise of how the statistical associations between blood group and some disease risks actually translate in vivo; evidence suggests that blood group antigens may play a biological role in some disease pathogenesis [ 7 ]. ABO antigen type has been postulated from many reports as a risk factor for some cardiovascular diseases [ 8 – 10 ], cancers [ 11 14 ], and infectious diseases [ 15 17 ]. The proposed mechanism believed to underlie how ABO blood group may influence cardiovascular disease risk involves the possible regulatory effect of ABO antigens on plasma levels of von Willebrand factor (VWF) and coagulation factor VIII (FVIII) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] and Afoakwah et al. [ 38 ], who recorded higher malaria prevalence for blood group O in Ghana. Another study suggested that the ABO blood group does not hinder the development of uncomplicated falciparum malaria but severe malaria [ 39 ].…”
Section: Discussionmentioning
confidence: 99%